Effectiveness of Accommodating Intra Ocular Lens - Muhammad Yusran (Fakultas Kedokteran Universitas Lampung, 2015)
Cataract surgery is effective in restoring distance vision. However, standard monofocal intraocular lenses (IOLs) have a fixed refractive power, leaving patients presbyopic and dependent on spectacles for near vision. Restoring the accommodative ability in pseudophakic patients is still challenging. This literature research focus to review the result of near visual acuity and amplitude of accommodation of available accommodating IOLs. Conducted from the Pubmed database and library research for journal articles that were published and related to accommodating IOLs using the keywords accommodating intraocular lens or monofocal intraocular lens or pseudophakic accommodation. Subjective and objective and measurement of amplitude of accommodation was observed. Subjectively, amplitude of accommodation is measured by defocus and near point of accommodation. Accommodation amplitude was measured by dynamic streak retinoscopy, power refractor and IOL movement objectively. Defocus measurement of accommodating IOL showed that the accommodative amplitude was between 0.94 D to 1.90 D and near point of accommodation (NPA) resulted in power around 0.5 D to 3.83 D meanwhile in the monofocal IOL, defocus power was between 0 to 1.52 D and NPA was between 0.42 D to 2.4 D. Dynamic retinoscopy of accommodating IOL showed power between 0.98 D to 0.99 D while monofocal IOL ranged between 0.17 D to 0.24 D. The movement of accommodating IOL was between 0.151 mm to 0.82 mm while it ranged between 0.02 mm to 0.4 mm for monofocal IOLs. Measurement by using power refractor showed that the power was between 0.39 D to 1.00 D for accommodatin IOL while it was 0.10 D to 0.17 D for monofocal IOL. Conclusion, accommodating IOL provided better near vision compared to monofocal IOL. [JuKe Unila 2015; 5(9):147-153]